National Palliative Care Policy: Challenges of Professional Qualification in Palliative Care in Brazil - Salman, Manuela Samir Maciel (2024)
The Brazilian Ministry of Health published the National Palliative Care Policy to alleviate the suffering of individuals with life-threatening illnesses and their family/caregivers. To promote quality of life and death, health professionals must be prepared/qualified to provide assistance that must integrate actions of varying degrees of complexity, proportional to the evolution of the disease. However, given the undeniable fragility of health professional education in regard to thanatology, death and palliative care in the country, one of the guidelines of this policy includes actions of encouraging the adoption of educational strategies in palliative care. For professionals to acquire skills for this type of assistance, more investment is needed to advance training at different levels of education quickly and efficiently, able to meet the population demands, the structure of the health system in every Brazil’s regions and the specificities of each profession.